A Feasibility Study of Optical Wireless Communication under Turbulent Conditions - WAQAS ABDUL SALAAM (University of Sindh Journal of Information and Communication Technology, 2019)
Free Space Optical Communication is one of the most emanate form of high data rates transmission. FSO communication system has the ability to fulfill the craving demand of high data rate users. It has the potential for both indoor and outdoor communication links. But there are multiple factors which demean the performance of FSO communication link. The optical communication link is highly affected by the Scattering, Scintillation, Refraction and Turbulence which degrade the execution of optical link in outdoor environment. FSO can be intensively employed as back-hall communication link to join data communication terminals due to its ease of deployment, license free long range operation, high bit rates, full duplex operation, protocol transparency and immunity to electromagnetic interference. The optical radiations which travel through atmosphere spread out and suffer from propagation losses. Some part of radiation is absorbed while other is scattered in the form of optical losses. This paper proposes a technique by which the reliability of the communication system can be improved by adjusting the transmitting parameters like transmitting wavelength. The conditions and physics of atmosphere cannot be changed but the signal propagation parameters can be adjusted. The contribution of the author is to develop an efficient transmission network which contains an optical transmitter and an optical receiver. There exists an outdoor channel link in between these. The uthor adopt an approach to achieve a reliable mode of communication in the operation of FSO link under turbulent conditions by utilizing previously developed models. Therefore; an important parameter transmitting wavelength is varied and its corresponding variations in the evaluating parameters like SNR and BER are observed and analyzed. Finally, a best transmitting wavelength window has been devised for the best operation of FSO Link under turbulent conditions.